2012
DOI: 10.1371/journal.pntd.0001805
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemicals against Malaria, Sleeping Sickness, Leishmaniasis and Chagas Disease

Abstract: In tropical regions, protozoan parasites can cause severe diseases with malaria, leishmaniasis, sleeping sickness, and Chagas disease standing in the forefront. Many of the drugs currently being used to treat these diseases have been developed more than 50 years ago and can cause severe adverse effects. Above all, resistance to existing drugs is widespread and has become a serious problem threatening the success of control measures. In order to identify new antiprotozoal agents, more than 600 commercial agroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 41 publications
(42 reference statements)
1
51
0
5
Order By: Relevance
“…Tolfenpyrad was included in the MMV ‘Pathogen Box’ based on results from a compound screen of agro-chemicals, which showed that tolfenpyrad has potent and selective in vitro activity against Trypanosoma spp. (Witschel et al., 2012). As a pesticide, tolfenpyrad has relatively broad activity against egg, larval, nymphal and adult stages of various arthropods (including Hemiptera, Coleoptera, Diptera, Lepidoptera, Thysanoptera and Acarina), and has been applied to various infested crops (Song et al., 2012, Yamaguchi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolfenpyrad was included in the MMV ‘Pathogen Box’ based on results from a compound screen of agro-chemicals, which showed that tolfenpyrad has potent and selective in vitro activity against Trypanosoma spp. (Witschel et al., 2012). As a pesticide, tolfenpyrad has relatively broad activity against egg, larval, nymphal and adult stages of various arthropods (including Hemiptera, Coleoptera, Diptera, Lepidoptera, Thysanoptera and Acarina), and has been applied to various infested crops (Song et al., 2012, Yamaguchi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no commercial vaccines available against most of these diseases (Pedrique et al., 2013, Hotez et al., 2016), diagnostic methods frequently suffer from insufficient specificity and sensitivity (Utzinger et al., 2012, Assefa et al., 2014), and treatments are often not highly effective and/or are toxic (Castro et al., 2006, Witschel et al., 2012, Molina et al., 2015). In addition, often the small numbers of drugs (or drug classes) frequently used, limited use of combination drug therapies and the implementation of mass drug administration programs bear the risk of drug resistance emerging in some groups of target pathogens (Humphries et al., 2012, Witschel et al., 2012, Webster et al., 2014). Therefore, the development of new drugs is crucial to ensure effective and sustained treatment and control into the future.…”
Section: Introductionmentioning
confidence: 99%
“…One of the exceptions is fluconazole, a fungicide product discovered by the pharmaceutical sector that is now used as a pharmaceutical but also was patented as a chemical with applications in crop production. [29][30][31][32][33][34] Bioavailability is highly important for any bioactive agent. The Lipinski's Rule of Five [35] can be considered as the reference for defining physicochemical and structural parameters for oral drug bioavailability.…”
Section: Similarity Of Drugs and Agrochemicalsmentioning
confidence: 99%
“…Um beide Felder zu bearbeiten, wurden Leitstrukturen aus der agrochemischen Forschung gegen infektiçse Keime getestet. [3] Während Säugetiere ausschließlich den Mevalonat-abhängigen Biosyntheseweg zu den Terpenoidvorstufen Isopentenyldiphosphat (IPP) und Dimethylallyldiphosphat (DMAPP) verwenden, [4] benutzen Pflanzen und viele humane Pathogene den Mevalonat-unabhängigen (auch 1-Desoxy-d-xylulose-5-phosphat (DXP) genannten) Biosyntheseweg, der in den 1990er Jahren entdeckt wurde.…”
unclassified
“…[12] Darüber hinaus wurden diese Derivate in vitro auf ihre Wirksamkeit gegen Plasmodium falciparum getestet. Die herbizide Aktivität der Pseudiline wurde bereits beschrieben, [3] und hier werden deren allosterische Bindungseigenschaften auf atomarer Ebene mittels Rçntgen-kristallographie an AtIspD-Komplexstrukturen aufgezeigt, wobei effektive Protein-Ligand-Halogenbindungsinteraktionen gefunden wurden.…”
unclassified